The Skandapurāṇa: Volume 4 / Adhyāyas 70-95, Start of the Skanda and Andhaka cycles / critical edition with an introduction & annotated English synopsis by Peter C. Bisschop and Yuko Yokochi ; in cooperation with Yuko Yokochi and Judit Törszök - Bisschop, Peter Christiaan; Yokochi, Yūko; Acharya, Diwakar; Törzsök, Judit (The Skandapurāṇa, 2018)
Preliminary Material /Peter C. Bisschop and Yuko Yokochi -- Introduction /Peter C. Bisschop and Yuko Yokochi -- Synopsis /Peter C. Bisschop and Yuko Yokochi -- Bibliography and Indexes /Peter C. Bisschop and Yuko Yokochi.